Epidemiological Determinants of Unmet Need for Family Planning Among Eligible Couples in Ahmedabad (GAIMS Journal of Medical Sciences, 2025)
BackgroundThe unmet need for family planning (FP) refers to the disparity between reproductive intentions and contraceptive behavior. According to NFHS-5, the total unmet need for FP is 10.3% among newly married couples in Ahmadabad, with higher rates in rural (10.8%) than urban (9.7%) areas of Gujarat. This study is conducted to identify the epidemiological determinants of unmet need for family planning among eligible couples in Ahmadabad and assess of U-PHC for provision of family planning services.MethodologyA community-based cross-sectional study was conducted among married women (18-49 years) in 7 AMC zones. Stratified cluster sampling (n=900) was used, with 30 women selected from each of 30 UHCs, representing slum, slum-like, and non-slum areas. One-on-one interviews were conducted using an open-ended questionnaire." Interview of MO with filling up of checklists of 14 UPHC from 7 zones of AMC (2 centers each).ResultsAmong married women, 74% expressed demand for family planning, with 67% seeking spacing and 7% seeking limiting. Nonusers exhibited an unmet need 30%, associated with significantly poorer FP knowledge (p < 0.05)." All 14 centers had organized an average 137 health and nutrition day in last 3 months; FP and methods of contraception were discussed by ANM. Supervision and counselling of FP found poor.ConclusionsThe study found a 30% unmet need for family planning among participants, with significant knowledge gaps, building and infrastructure is good in all except one U-PHC. Supervision found to be poor in all selected U-PHC’s.